The China Challenge: Sino-Canadian Relations in the 21st Century - (:unkn) unknown (Les Presses de l'Université d'Ottawa / University of Ottawa Press, 2011)
With the exception of Canada’s relationship with the United States, Canada’s relationship with China will likely be its most significant foreign connection in the twenty-first century. As China’s role in world politics becomes more central, understanding China becomes essential for Canadian policymakers and policy analysts in a variety of areas. Responding to this need, The China Challenge brings together perspectives from both Chinese and Canadian experts on the evolving Sino-Canadian relationship. It traces the history and looks into the future of Canada-China bilateral relations. It also examines how China has affected a number of Canadian foreign and domestic policy issues, including education, economics, immigration, labour and language. Recently, Canada-China relations have suffered from inadequate policymaking and misunderstandings on the part of both governments. Establishing a good dialogue with China must be a Canadian priority in order to build and maintain mutually beneficial relations with this emerging power, which will last into the future.
1. Introduction: Canada’s Response to China’s Increasing Role in the World (Huhua Cao) 2. Canada’s Staying Power: A Diplomat’s View (Fred Bild) 3. The Canadian Policy Context of Canada’s China Policy since 1970 (Charles Burton) 4. Canada and China: The China Strategy of 1987 (B. Michael Frolic) 5. The Politics of Soft Power in Sino-Canadian Relations: Stephen Harper’s Visit to China and the Neglected Hong Kong Factor (Sonny Shiu-Ling Lo) 6. Friends across the Pacific: Links between Canada and Hong Kong in Historical and Contemporary Perspectives (Ming K. Chan) 7. Canadian and Chinese Collaboration on Education: From Unilateral to Bilateral Exchanges (Qiang Zha) 8. Canada and China after the Global Financial Crisis (Yuen Pau Woo) 9. Post-Colonial Transformations in China’s Hong Kong and Macau: Implications for Cross-Taiwan-Strait and Canada–PRC Links (Vivienne Poy) 10. Hong Kong: Canada’s Partner in Prosperity (Perrin Beatty) 11. The Transformative Effects of the Global Economic Crisis: Implications for the World and Shanghai’s Aspirations (Thomas d’Aquino) 12. The Canadian Constitution and the Charter of Rights and Freedoms: A Global Template for Minority Rights with Relevance to China? (Errol P. Mendes) 13. Chinese in Canada and Canadians in China: The Human Platform for Relationships between China and Canada (Kenny Zhang) 14. Transnational Intergenerational Support: Implications of Aging in Mainland China for the Chinese in Canada (Ghazy Mujahid, Ann H. Kim and Guida C. Man) 15. The Bridge Too Far?: Language Retention, Ethnic Persistence, and National Identification among the Chinese Diaspora in Canada (Jack Jedwab) 16. Changing Territorial Strategies: Chinese Immigrants in Canada (Huhua Cao and Olivier Dehoorne) 17. Causes and Consequences: Overeducated Chinese Immigrants in the Canadian Labour Market (Tony Fang) 18. Conclusion: Reimagining Canada’s Present and Future in the Shadow of the Rise of China (Jeremy Paltiel)